Pericardial Anatomy, Interventions and Therapeutics: A Contemporary Review. Issue 6 (2nd November 2021) - Reyaldeen, Reza; Chan, Nicholas; Lo Presti, Saberio; Fava, Agostina; Anthony, Chris; Rodriguez, E. Rene; Tan, Carmela D.; Saliba, Walid; Cremer, Paul C; Klein, Allan L.
ABSTRACT: Pericardial access, predominantly utilized for emergency treatment, has evolved as an important approach for performing cardiac interventions. Accordingly, the complex anatomy and unique physiology of the pericardium need to be well understood for procedural success. This understanding is important to not only plan and guide interventions but also to inform complications and morbidity associated with post-cardiac injury syndromes. In these circumstances, multi-modality imaging has an increasingly central role. Therefore, the aims of this review are to provide an overview of procedurally relevant pericardial anatomy and focus on important imaging assessments as they relate to the increased use of pericardial access for intervention and possible consequences in patients who develop post-cardiac injury pericarditis.